The role of fiscal policy in a monetary union : are National automatic stabilizers effective? - Andrea Colciago; Vito Antonio Muscatelli; Tiziano Ropele; Patrizio Tirelli (Center for Economic Studies and ifo Institute (CESifo), 2006)
We assess the role of national fiscal policies, as automatic stabilizers, within a monetary union. We use a two-country New Keynesian DGE model which incorporates non-Ricardian consumers (as in Gal? et al. 2004) and a home bias in the composition of national consumption bundles. We find that fiscal policies stabilize the aggregate economy but, in some cases, generate conflicting views among national policymakers. Finally, model determinacy requires that national fiscal feedbacks on debt accumulation be designed with reference to the debt dynamics of the entire monetary union. This is in sharp contrast with the "Brussels consensus" based on the view that the ECB alone should stabilize the union-wide economy and national fiscal policies should react to idiosyncratic shocks and to national debt levels.
Keywords: E58; E63; E62; 330; Finanzpolitik; Eingebauter Stabilisator; Währungsunion; Ungleichgewichtstheorie; Allgemeines Gleichgewicht; Zwei-Länder-Modell; Theorie; EU-Staaten